PTU-146 Dual energy x-ray absorptiometry (DEXA) scans in coeliac disease (CD): are BSG guidelines followed?. (28th May 2012) - Krishnan, B; Sehgal, V; Ramdass, D; Besherdas, K
Abstract : Introduction: Patients with CD have a higher incidence of osteopenia or osteoporosis due to reduced bone mineral density (BMD). However, significant improvement in BMD and calcium absorption is seen after introduction of gluten-free diet (GFD). The BSG recommend (with poor evidence) that DEXA scan should only be performed after introduction of GFD in patients with high risk (two or more of the following: age >70, low BMI, weight loss more than 10 kg and those with persistent symptoms on GFD for a year or non-compliance with diet). The aim of this study was to look at our practice of DEXA scanning in CD patients and assess whether BSG guidelines were followed and whether the timing of DEXA scans made any difference to outcome. Methods: We reviewed all 82 patients from our coeliac database who were diagnosed between April 1985 and November 2011 at a district general hospital in North London (Chase Farm Hospital). 14 patients were excluded from the study as medical notes were missing or they were lost to follow-up. Two patients did not have DEXA scan. Data were analysed retrospectively by review of medical and electronic records. Patient demographics, BMI, history of weight loss, age at diagnosis, date of DEXA scan and results were recorded. We used the standard WHO definition for osteoporosis (T score < −2.5), osteopenia (T score between −1 and −2.5) and normal (T score > −1). Results: The mean patient age was 54 (range 19–93) with 52 females. The mean time interval between diagnosis and DEXA was 2 years and 10 months (range 0 month–33 years) with a median of 8 months. 37 patients (56%) had DEXA scan within a year of diagnosis of which 16 (43%) were normal, and the rest had osteopenia (24%) or osteoporosis (32%). Of the remaining patients (45%), nine had normal DEXA, five had osteopenia and 11 had osteoporosis. Comparing these two groups of patients the timing of DEXA scan (1 year of diagnosis) was not statistically significant in terms of outcome (p value—1.0000). However 80% of patients over the age of 70 years had osteoporosis. There was no record of BMI, history of weight loss or other risk factors for osteoporosis prior to DEXA request. Conclusion: Our practice of DEXA scan did not adhere to the BSG guidelines. There was great variability in timing of DEXA scans in CD patients. There was marked absence of record keeping in terms of BMI, history of weight loss and other risk factors to guide DEXA requests. A large proportion of patients (80%) with CD over age of 70 had osteoporosis. The timing of the DEXA scan did not significantly affect the T score. The lack of adherence to guidance could be because of its poor evidence base and also there is no clear recommendation on repeat DEXA scanning following initial assessment. We would recommend clearer guidance on the assessment of osteoporosis in CD. Competing interests: None declared.